Modern approach in oligometastatic prostate cancer therapy - Stanić, Jelena; Stankovic, Vesna; Nikitovic, Marina (Medicinski podmladak, 2022)
The oligometastatic stage of cancer spread has been described as a step in between localized malignancy and extensive metastases. Patients with advanced prostate cancer can present with both widespread metastatic or oligometastatic diseases. Oligometastatic prostate cancer, generally defined by the presence of five or fewer metastatic sites on imaging.In the era of precision and personalized cancer care, the introduction of more sensitive imaging technologies and the availability of safe and effective localized non- or minimally invasive treatment options, have led to an increase in the incidence and clinical interest in oligometastatic prostate cancer. In addition, the therapeutic paradigm for oligometastatic prostate cancer is evolving toward a more aggressive approach. Retrospective studies have shown that in the metastatic setting, treatments such as radical prostatectomy and local or metastasis-directed radiation therapy can be performed with minimal risk of toxicity and may enhance clinical outcomes. As there is insufficient data to draw reliable conclusions about their impact on survival, aggressive approaches in the treatment of oligometastatic prostate cancer should be considered only in the context of prospective clinical trials, with the patient informed of the limited evidence of benefit.The current inconsistent approach of detecting and treating oligometastatic prostate cancer patients will need to be standardized in order for future clinical studies to be properly performed and, more importantly, compared. These crucial conditions will reveal if oligometastasis diagnosis and therapy should be included in the standard clinical practice of prostate cancer patients.
Keywords: prostate cancer; oligometastasis; radiotherapy